Phytoremediation of battery industry effluent through aquatic macrophytes - Rashid, Mahrine; Ahmad, Iftilkhar; Muhammad, Ashique; Ul Hassan, Mahmood (International Journal of Biological Research, 2020)
Research was conducted to quantify the level of copper (Cu), chromium (Cr), cadmium (Cd) and lead (Pb) contamination in battery industry effluent and to assess the remediation potential of three invasive aquatic macrophytes Eichhornia crassipes, Pistia stratiotes and Hydrocotyle umbellata by growing on industrial effluent collected from Lead acid Battery industry.The effluent was heavily contaminated with Pb (10mg/l) and sulphuric acid (pH 2- 2.1). Due to high Pb concentrations and low pH (2-2.2) the plants were unable to survive. Mortality rate of E. crassipes was 96 % while P. stratiotes and H. umbellata were 100% rotten. The experiment was repeated after adjusting the effluent pH to 7-7.5 to increase the plant life.Plant parts and wastewater samples were analyzed after every 3 days interval uptil 21st day. The amount of Cr, Cd and Cu in the effluent was 0.076 mg /L, 0.036 mg /L and 0.097 mg /L, which was in permissible limits of NEQs (1.0 mg/l, 0.1 mg/l and 1.0 mg/l) respectively. Pb was found 10 times higher i.e. 10 mg/l than the permissible limit 0.5 mg/l. E. crassipes removed Pb>Cr>Cu>Cd while P. stratiotes and H. umbellata reduced Cd, Cr, Cu more than Pb from the effluent. E. crassipes was most efficient Pb removing plant in 21 days of experiment.Â Â